Driving Innovative Work Behavior Among University Teachers Through Work Engagement and Perceived Organizational Support - Pouya Zargar; Amira Daouk; Sarah Chahine (Administrative Sciences)
Leaders are critical players in determining how their employees behave in the workplace. Particularly in higher education, teachers are required to utilize psychological, social, and physical resources to perform their tasks. This, along with institutional limitations, renders the role of ethical leaders more critical for driving positive performance outcomes. In this context, the current study investigates the role of ethical leadership on innovative work behavior of university teachers in Turkey. To provide a better understanding, mediating effect of work engagement and the moderating impact of perceived organizational support are also analyzed. With a total of 211 surveys gathered in a cross-sectional manner and using partial least squares—structural equation modeling with Smart-PLS software—the hypotheses were tested. By embedding social exchange, self-determination, and organizational support theories, the current study highlights the importance of the unique characteristics of ethical leaders in academia as antecedents of innovation for teachers, implementing long-term positive changes in the faculty. When institutional support systems exist, faculty deans can trigger engagement by leveraging the facilities and initiatives of the university, ultimately enhancing the learning environment of students while tending to the wellbeing of academic staff.